The Effect Of A Solution-Centered Counseling Program In Reducing Electronic Blackmail Among Female University Students (Journal of the College of Basic Education, 2024)
The current research aimed to identify electronic blackmail among female university students, and to identify the impact of the counseling program (solution-centered counseling). To achieve the objectives of the current research, the following null hypotheses were derived: There is no statistically significant difference at the significance level (0.05) between the average scores of the experimental group members in the pre- and post-tests on the electronic blackmail scale among female university students, and there is no statistically significant difference at the significance level ( 0.05) between the average scores of the control group members in the pre- and post-tests on the electronic blackmailing scale among female university students, and there is no statistically significant difference at the significance level (0.05) between the average scores of the experimental and control group members in the post-test on the electronic blackmailing scale among female university students, In order to identify the effect of the solution-centered counseling program in reducing electronic blackmail among female university students, the limits of the research were all female students of the College of Basic Education/Al-Mustansiriya University for morning and evening study for the academic year ( 2023-2024). In order to achieve the objectives and hypotheses of the current research, the researchers adopted the experimental method. The sample of the experiment was (20) female students, and the researchers adopted the design of the experimental groups and the control group with pre- and post-tests. Equivalence was made between the experimental and control groups in the variables (age, father’s achievement, mother’s achievement, and the female students’ scores on the electronic blackmail scale), and the researchers adopted a scale Electronic blackmail and the construction of a counseling program (solution-centered psychological counselling). The researchers verified the psychometric properties of the scale by analyzing its items visually and statistically, and also calculated its reliability in two ways (test and retest, Cronbach). Validity was verified with indicators of apparent validity and construct validity. The second is constructive The brief psychological counseling program. The research reached a set of results, including: There are statistically significant differences between the average scores of individuals in the experimental group in the pre- and post-tests on the electronic blackmail scale after applying the counseling program. This difference is in favor of the experimental group, that is, a function in favor of the post-test. There are no significant differences. There is statistical significance between the average scores of the members of the control group in the pre- and post-tests on the electronic blackmail scale. This is an indication that the control group was not affected and the variables were controlled for not being exposed to the counseling program. It was also found that there are statistically significant differences between the average scores of the members of the experimental group and the control group in Post-test on the electronic blackmail scale after applying the counseling program. The counseling program (solution-centered psychological counseling) also proved to have a significant impact in reducing electronic blackmail, as the effect size reached (0.612), which is a large value. The research came out with a set of recommendations and proposals.